Motivasi Pemilihan Lintas Minat Sains pada Siswa Jurusan Ilmu Sosial - Yendrita Yendrita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to find out how intrinsic and extrinsic motivation affects students of the Social Sciences Department of SMA N I Suliki District in choosing cross-interest of Science. This type of research is quantitative research with descriptive methods. The research instrument is a set of questionnaire. Samples were taken with a total sampling technique, then the subjects of this study were all students of class X majoring in Social Sciences who chose cross interest of Science, amounting to 126 people, data analysis technique is a percentage technique. Based on the results of data analysis, intrinsic motivation that influences the selection of cross-student interests is as follows: based on ideals of 70.58%, based on student abilities of 69.44%, based on student conditions of 70.33%, based on interests of 66.93 %, based on the attitude of 75.06%, while extrinsic motivation that influences the selection of students' cross-interest is as follows; based on family encouragement of 62.56%, encouragement of friends 59.32%, employment opportunities of 69.57% and opportunities to continue study 61.50%. Whereas based on sub-variables, intrinsic motivation was found to influence the cross-selection of scientific interest by 70.48% (in the good category) and extrinsic motivation by 62.75% (in the good category). The conclusions of this study are: intrinsic motivation influences students more in crossing scientific interests than extrinsic motivation Keywords: Motivation, SAINS Cross-Interest Selection,